IDENTIFICATION OF TEACHERS' PROBLEMS IN USING AI (ARTIFICIAL INTELLIGENCE) TECHNOLOGY IN THE LEARNING PROCESS AT MAN 01 KOLAKA - Juwirda, Juwirda; oktavia, komang opie; Asriani, Sari; Afdal, Muhamad; Aditya, Muhammad Radit; Nurdin, Nurdin; Amanah, Siti; Jaya, Irfan; Hasna, Wa; Hariyadi, Eko (USN Kolaka, 2024)
This study aims to identify the problems faced by teachers in using artificial intelligence technology (AI) in the learning process at MAN 01 Kolaka. The main focus of the research is to examine the inhibiting factors, such as lack of understanding of technology, accessibility, and readiness of educational infrastructure. Using a qualitative descriptive approach, data were collected through interviews, observations, and documentation. The instruments used were observation sheets and interview guidelines. This research was conducted at MAN 1 Kolaka with 10 teachers as research subjects. The data analysis technique used is a qualitative data analysis technique according to Miles and Huberman. The results show that while AI has great potential to improve the quality of learning, several key obstacles, including limited teacher training and resistance to new technologies, are challenges that must be overcome. Research recommendations include the development of AI technology training programs for teachers and the improvement of supporting facilities in schools.